(3eMGVQGJ aj ebjGS GdeYGjjQ GdeMGSHjI GdOhdjI (BIAS/IFRS : s (3eWHhYI ehLgI daGFOI GdWdHI d e O (B: (3SfI KGfjI djSGfS JNUU eGdjI h eMGSHI (B/ s - (3BefI, JhfSjs; (3LGeYI GdLRGFQ(B3: (3cdjI GdYdhe GdEbJUGOjI, GdYdhe GdJLGQjI hYdhe GdJSjjQs ((3GdLRGFQs (3LGeYI GdLRGFQ(B3: (3cdjI GdYdhe GdEbJUGOjI, GdYdhe GdJLGQjI hYdhe GdJSjjQs, 2021)
(3GdJhLg GdOhdj fMh eYGjjQ GdeMGSHI GdOhdjI, GdeYGjjQ GdeMGSHjI GdOhdjI GdeJHfGI ef WQa GdfXGe GdeMGSHj GdeGdj, GdeYjGQ GdeMGSHj GdOhdj Qbe (BIAS01 (3YQV GdbhGFe GdeGdjI, GdeYjGQ GdeMGSHj GdOhdj Qbe (BIAS07 (3bGFeI GdJOabGJ GdfbOjI(B.s
(3GdeQGLY U(B.185s
Keywords: (3GdGehGds; (3GdeMGSHIs